2023
DOI: 10.3389/fpls.2023.1219139
|View full text |Cite
|
Sign up to set email alerts
|

Active permanent greening – a new slope greening technology based on mineral solubilizing microorganisms

Lingjian Wang,
Xinggang Tang,
Xin Liu
et al.

Abstract: IntroductionWith social and economic development and the associated large-scale exploitation of natural resources, the number of slopes has significantly increased. As slope instability can lead to serious geological disasters, the ecological protection and reconstruction of slopes has become a hot topic of common global concern.MethodsIn order to achieve scientific slope management and overcome the difficulty of maintaining slope greening in the long term, this study explored eight strategies (A, B, C, AB, AC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 81 publications
(96 reference statements)
0
2
0
Order By: Relevance
“…Jia et al further investigated the screened microorganisms and found that a variety of MSMs could promote root growth, increase root strength, increase the number of root nodules, and affect the number and species of inter-root microorganisms (Jia et al, 2021) on the nitrogen cycling with extremely significant effects (Li C. et al, 2020;Li et al, 2021a;Li et al, 2021b). In addition, we conducted a series of optimization studies on slope spraying substrates, including water retention agents (Wang L. et al, 2022), comprehensively analyzed and ranked the effects of different treatments, and preliminarily applied the MSM-based APG method (Wang L. et al, 2023). The results showed that APG was an effective and feasible slope greening method, with great application value and broad application prospects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jia et al further investigated the screened microorganisms and found that a variety of MSMs could promote root growth, increase root strength, increase the number of root nodules, and affect the number and species of inter-root microorganisms (Jia et al, 2021) on the nitrogen cycling with extremely significant effects (Li C. et al, 2020;Li et al, 2021a;Li et al, 2021b). In addition, we conducted a series of optimization studies on slope spraying substrates, including water retention agents (Wang L. et al, 2022), comprehensively analyzed and ranked the effects of different treatments, and preliminarily applied the MSM-based APG method (Wang L. et al, 2023). The results showed that APG was an effective and feasible slope greening method, with great application value and broad application prospects.…”
Section: Discussionmentioning
confidence: 99%
“…Given the great potential of microorganisms in the revegetation of slopes, we proposed an active permanent greening (APG) method based on selected mineral solubilizing microorganisms (MSMs) (Wang L. et al, 2023). We isolated a variety of microorganisms from the dolomite rock wall of the Mufu Mountains, Nanjing, and selected four typical strains (Jinchi et al, 2014;Guanglin et al, 2015;Jinchi et al, 2015a;Jinchi et al, 2015b) for use in slope management after preliminary experiments on cultivation and solubilization mechanisms.…”
Section: Introductionmentioning
confidence: 99%